(untitled) (Nordic Journal of African Studies, 2000)
This article analyses counter-banditry policies during the British military administration of Eritrea from 1941 to 1952. The study dismisses the claim that post-Second World War Eritrea was too fragmented along ethnic and religious lines to be allowed to gain political independence. Its finding is that such claims were calculated to influence the political future of the territory through an international compromise deal that allowed Ethiopia to administer, and later to colonize Eritrea. Britain’s counter-banditry measures failed because she did not deliver the liberation promises made to the people of Eritrea during the World War, there was little investment in will and resources, and her wider imperialistic designs in the Horn of Africa came on the way. The article concludes that, whatever the ethnic or religious identity of Shifta bandits, the causes, course, and resolution of banditry could not be isolated from the uncertainty and complexity of determining Eritrea’s sovereignty. Hence the political protest that was treated as banditry during the British Military Administration of Eritrea from 1941 to 1952 crystallized into four decades of formidable liberation struggle against Ethiopia’s administration.